Catastrophic models of materials destruction; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Kupchishin A. I. Anatoliy Ivanovich; Taipova B. G.; Kupchishin A. A.; Voronova N. A.; Kirdyashkin V. I.; Fursa T. V. Tatyana Viktorovna (2016, 2016)
Title screen